A new surgical concept for the efficient treatment of large and deep burns - Hundeshagen, Gabriel; Panayi, Adriana C.; Hannmann, Torsten T.; Knoedler, Leonard; Tapking, Christian; Palackic, Alen; Haug, Valentin; Bliesener, Björn; Vogelpohl, Julian; Vollbach, Felix Hubertus; Kneser, Ulrich (Journal of burn care & research, 2025)
Effective burn surgery is based on two fundamental principles: prompt excision of necrotic tissue and definitive coverage, preserving functional dermis and body contour. There is often compromise, either prioritizing the urgency of excision or opting for patient stability and optimal conditions prior to autografting. We propose a surgical concept that addresses this critical treatment gap. In 2022, we implemented a new three-phase protocol, EDM: (Excision phase, E) Immediate excision of the burn wound preserving body contour; (Dermis phase, D) definitive temporization of the wound bed, using biodegradable temporizing matrix, to prepare it for successful grafting. Upon complete dermal temporization, full autologous coverage in a single micrografting procedure is achieved (Meek phase, M). We performed a retrospective single-center cohort study to characterize the EDM protocol compared to the prior standard of care (>40% TBSA, n = 5 in EDM vs n = 10 matched controls). Primary outcomes were total surgeries required, total surgeries to achieve>90% healing, uninterrupted recovery time without surgery, and time on mechanical ventilation. The EDM group required fewer surgeries in total (5 vs 9.5; P = .01) and to achieve>90% healing (3 vs 6.5; P = .001). EDM patients experienced longer uninterrupted recovery (25 vs 13 days, P = .001). Additionally, EDM patients spent less time on mechanical ventilation (210 vs 1136 h, P = .005). The EDM protocol could improve surgical efficiency, ultimately having the potential to expedite rehabilitation for severely burned patients. The study underscores the potential of combining the fundamentals of burn surgery, with innovative surgical techniques and materials, in order to bridge the gap between excision and grafting.
Veröffentlicht: 5. Juni 2024, korrigiert und Schrift gesetzt: 10.Juli 2024
Gesehen am 10.12.2024